The role of economic freedom in R&D spillovers via student flows - Tee, Chee Lip; Wan Ngah, Wan Azman Saini; Ibrahim, Saifuzzaman (Faculty of Economics and Management, UKM, 2014)
This paper examines the mediating effect of economic freedom on the research and development (R&D) spillovers effect via the international student flow channel in a panel of 75 developing countries. The empirical results, based on generalized method-of-moment system estimator, found that spillovers effects through import and international flow are both positive and significance. Nevertheless, the strength of spillovers is different from previous findings, where spillovers through international student flow is found greater. It provides evidence for the view that importance of human capital mobility in technology diffusion is increasing nowadays since globalization lead the mobility across border become easier. Meanwhile, the results also suggest that countries with greater economic freedom would benefit more from disembodied spillovers.